What waits in the woods - Scott, Kieran, 1974- (Point, an imprint of Scholastic, Inc., 2015)
A hiking trip in the woods in upstate New York is out of the comfort zone for sixteen-year-old city girl Callie Velasquez, but she wants to bond with her new friends Lissa and Penelope, not to mention her new boyfriend, Jeremy. However, nothing could have prepared her for the true human darkness that waits for her in the wood.